P364 Stopping azathioprine in monotherapy after very prolonged remission in inflammatory bowel disease patients: Novel relapse risk factors. (16th January 2018) - Iborra, M; Herreras, J; Boscá-Watts, M; Cortés, X; Trejo, G; Beltran, B; Cerrillo, E; Minguez, M; Nos, P
Abstract: Background: When to stop immunosuppressive therapies after long-term remission remains controversial. The aim of this study was to determine the best moment for withdrawal of azathioprine (AZA) in sustained remission and to identify potential predictors of relapse. Methods: A Spanish multicentre study including 95 inflammatory bowel disease (IBD) patients, 60 Crohn`s disease (CD) and 35 ulcerative colitis (UC) patients, who have stopped AZA treatment while in prolonged remission for at least 4 years. We collected demographic and clinical data. The presence of clinical and/or endoscopic remission and biologic values (C - reactive protein (CRP), fecal calprotectin (FC) and haemoglobin (Hb) levels) at AZA interruption were also collected. FC and CRP level measurements were assessed at 6 and 12 months in order to monitor the remission. Results: The characteristics of the population are shown on Figure 1. Only 5 CD patients received previous anti-TNF treatment. Morphologic remission was evaluated by colonoscopy or magnetic resonance enterography in 23 UC (66%) and 35 CD (58%) patients. After AZA discontinuation 32 UC (91%) and 40 CD (67%) patients were treated with high doses of salicylates (>3 g). Time-to-relapse rate as a function of time after AZA withdrawal is showed in Figure 2. Overall, 26 patients relapsed (9 UC, 26%, and 17 CD, 28%). The cumulative relapse rates at 1, 2, 3, and 5 years were 23%, 28%, 28%, and 46%, respectively, in UC patients and 12%, 20%, 24% and 46%, respectively, in CD patients. Among the 26 relapsing patients, 19 were retreated by AZA and 14 successful remissions. UC patients who had relapsed had less colonoscopy prior to withdrawal (56% vs. 31%). Prior surgery in CD was not associated with a higher percentage of relapse. Maintenance treatment with salicylates could avoid relapse in CD. No relapse was observed in the 14 patients with AZA as prevention of recurrence. The steroid-dependence status and the late and early introduction of AZA in UC and CD respectively were predictors of relapse Conclusions: In clinical practice, almost half of the IBD patients who stop AZA therapy remain in remission at 5 years. Salicylates may be useful after withdrawal, even in CD. Previous steroid-dependence status, prior surgery, the timing time of AZA introduction, and the indication can help us decide the better candidate to withdrawal AZA treatment.